Stewart L. Udall papers - Udall, Stewart L.; Frost, Robert, 1874-1963.
Two signed typescripts with holograph corrections of Robert Frost's poem, "Dedication," written for the presidential inauguration of John F. Kennedy in 1961. Includes the original typescript and a revised version prepared by Frost for inclusion in his book, In the Clearing (1962), under the title "For John F. Kennedy His Inauguration." Includes a note (1969 December 30) written by Udall concerning the drafts of Frost's poem, both of which were inscribed to Udall.
U.S. secretary of the interior, lawyer, and author. Born 1920.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Kennedy, John F. -- 1917-1963 -- Inauguration, 1961.; American poetry; Authors; Cabinet officers; Lawyers